Towards smoke-free cars in the Republic of Korea: Evidence from environmental and biochemical monitoring of third-hand smoke exposure in taxis - Park, Eun Young (Tob Induc Dis, 2018)
INTRODUCTION: To evaluate the level of tobacco smoke exposure in taxis in Korea using tobacco specific environmental markers. METHODS: From June to September 2012, cross-sectional measurements of air nicotine levels and dust nicotine-derived nitrosamine ketone (NNK) concentrations were conducted in 17 taxis in Goyang, Korea. Field investigators completed an observational questionnaire on building characteristics, smoking policies and evidence of smoking. Descriptive statistics including geometric means (GMs) ± standard deviations were produced for air nicotine levels and dust NNK concentrations. RESULTS: There was no evidence of active smoking in the 17 taxis monitored, despite the fact that 10 drivers were current smokers. The overall GMs of air nicotine and dust NNK concentration were 0.42 μg/m(3) and 6.78 pg/mg, respectively. These levels were 3.4-fold and 2.6-fold higher in taxis whose drivers were current smokers compared to the taxis of nonsmokers (GM of air nicotine: 0.65 μg/m(3) vs 0.19 μg/m(3); GM of dust NNK: 10.07 pg/mg vs 3.85 pg/mg). CONCLUSIONS: The present study shows that air nicotine and dust NNK were detected in all taxis regardless of whether the taxi driver was smoking or not, which indicates the potential for exposure to SHS or THS. It suggests that an appreciable level of SHS and TSH exposure might occur if the environment is not completely smoke-free and enforcement is lacking. ABBREVIATIONS: THS: third-hand smoke, SHS: second-hand smoke, FCTC: Framework Convention Alliance for Tobacco Control, NNK: 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone, LOD: limit of detection, GM: geometric mean, GSD: geometric standard deviation.